KINERJA DINAS KESEHATAN KOTA DENPASAR DALAM PEMBERDAYAAN ORANG DENGAN SKIZOFRENIA (ODS) DI RUMAH BERDAYA DENPASAR - Fitriana, Dina Ayu; Yudharta, I Putu Dharmanu; Winaya, I Ketut (CITIZEN CHARTER, 2019)
ABSTRACT Every organization needs to look for performance to determine which results have been achieved through the implementation of tasks that are given in accordance with the objectives set. In this case, Denpasar City Health Office seeks to provide services for schizophrenic patients (ODS) in obtaining a good healing process and improving the performance and quality of its empowermentprograme. However, in current practice there are problems arise as the impactof less optimal achievements that diversfrom the organization's vision. This study aims to determine the performance of Denpasar City Health Office in empowering people with schizophrenia (ODS) in RumahBerdaya Denpasar. This research used descriptive qualitative. The theory used performance theory of Mahsun 2006 which has six measurement indicators include; input, process, output, outcome, benefit, and impact.From the result obtained, showed that the performance of Denpasar City Health Office has not been good and ineffective, some inhibiting factors have been found that make the performance not optimal. It is necessary to evaluate the empowerment performance of Rumah Berdaya, so that the goals of empowerment can be achieved. Keywords: Organizational Performance, Empowerment of people with schizophrenia (ODS), Rumah Berdaya